1997
DOI: 10.5032/jae.1997.01046
|View full text |Cite
|
Sign up to set email alerts
|

Assessment Of Cognitive Discourse: A Study Of Thinking Opportunities Provided By Professors

Abstract: The American higher education system has been under close scrutiny for more than a decade. The cause is clear: a lack of correspondence between that which is believed to be requiredfor critical thinking in adulthood and that which universities are teaching. The purpose of this study, therefore, was to describe the opportunities given to students to reach higher cognitive levels through professors " classroom discourse. The researchers sought to explore relationships between classroom discourse and class size, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 11 publications
1
20
0
1
Order By: Relevance
“…This is consistent with previous research indicating that teacher discourse in college classrooms occurs primarily at the knowledge and comprehension levels of cognition. The knowledge and comprehension levels were represented in 73% (Whittington, Lopez, Schley, & Fisher, 2001), 80% (Whittington, Stup, Bish, & Allen, 1997), 85% (Miller & Newcomb, 1990), and 98% (Whittington, 1995) of instructor discourse in previous studies.…”
Section: Conclusion/recommendations/ Implicationsmentioning
confidence: 81%
“…This is consistent with previous research indicating that teacher discourse in college classrooms occurs primarily at the knowledge and comprehension levels of cognition. The knowledge and comprehension levels were represented in 73% (Whittington, Lopez, Schley, & Fisher, 2001), 80% (Whittington, Stup, Bish, & Allen, 1997), 85% (Miller & Newcomb, 1990), and 98% (Whittington, 1995) of instructor discourse in previous studies.…”
Section: Conclusion/recommendations/ Implicationsmentioning
confidence: 81%
“…This conclusion is consistent with Cano and Metzger (1995) who found secondary horticulture teachers taught at lower-levels of cognition 84% of the time. At the college level, lower-order behavior was found 61% (Ball & Garton, 2005), 98% (Whittington, 1995), and 80% (Whittington, et al 1997).…”
Section: Conclusion Implications and Recommendationsmentioning
confidence: 99%
“…Whittington (1995) recommended the exploration of "barriers to teaching at higher cognitive levels" (p. 37). Also, research (Whittington, Stup, Bish, & Allen, 1997) found that instructors were the most influential factor in creating the opportunities for students to think at higher levels of cognition. However, instructors' cognitive behavior was not found to be associated with their attitude toward teaching at higher cognitive levels (Whittington, 1991).…”
Section: Introduction -Theoretical Frameworkmentioning
confidence: 99%
“…Whittington and Newcomb (1993) and Whittington, Stup, Bish, and Allen (1997) recommend higher education students perform at higher levels of cognition -considering other related factors -but do not recommend a specific critical thinking level which students should achieve. We recommend that a goal for student teacher critical thinking is necessary, before analysis or assessment of critical thinking, in order to determine if online technologies can be used to enhance student teachers' critical thinking skills and abilities.…”
Section: Journal Of Agricultural Education 86 Volume 57 Issue 2 2016mentioning
confidence: 99%